The art of short form content from concept to color correction - Cook, Bryan 1976- (Focal Press, 2016)
"The art of short form content: from concept to color correction is an in-depth examination of the craft of creating short form filmic content -- a category which includes television commercials, music videos, television promos, movie trailers, digital billboards, corporate videos, and pretty much anything else with a running time under five minutes. Though short form is an important part of the film industry, it is typically overlooked in books on the art of filmmaking. The art of short form content fills the industry void by answering the type of questions that working short form creators deal with every day. As Cook explains, though short form content is limited in duration, it is not limited in quality and message." -- Provided by publisher